Aproximações interartes na Educação Infantil da Prefeitura de São Paulo: crianças pequenas e formas de exploração no encontro com livros ilustrados - Santos, Ana Barbara dos (2024)
This study purpose is to investigate, in illustrated books selected from the literary collection of Secretaria Municipal de Educação de São Paulo, from the years 2022 and 2023, their interarts potential for children. The question is how the materiality of children's books resizes aesthetic perception and supports meeting between arts and children at an Early Childhood Education Center in the city of São Paulo. Therefore, the corpus of study are three children's books: Dobras (2017), by Andrés Sandoval; Concerto de piscina (2021), by Renato Moriconi, and Migrantes (2021), by Isa Watanabe. Based on hypotheses such as: illustrated books for children operate the potential of arts, supporting meeting between arts in education; The illustrated books in study, become triggers of the interarts relationship, by bringing materiality and graphic design into narrative harmony. The aim is to test the research problem by observing the relationship between children and books. The study is based on authors such as Antônio Candido (2011), Adriana Friedman (2017), Edgar Morin (2011), Cecilia Salles (2011)_and Lev Vygotsky (2014). In addition to relying on Currículo da Cidade - Educação Infantil de São Paulo (2019) and Diretrizes Curriculares Nacionais para Educação Infantil (2010). The analysis presents the continuity relationships with books that provoke children to express themselves in multiple languages